Further evidence for the heterogeneity of functional muscarinic receptors in guinea pig gallbladder - AKICI, AHMET; KARAALP, ATİLA (My University, 2000)
Previous studies have suggested the presence of multiple muscarinic receptor subtypes in guinea pig gallbladder smooth muscle, although the relative abundance and functional role of these subtypes remains an area of significant research efforts. The present study utilized both radioligand kinetic and functional experiments to further probe the nature of the muscarinic receptors in gallbladder smooth muscle and their mode of coupling to intra- and extra-cellular Ca(2+) sources. Dissociation kinetic studies using [3H]N-methylscopolamine ([3H]NMS) indicated that the binding profile in guinea pig gallbladder smooth muscle could not be reconciled with that expected for a single muscarinic receptor subtype, the latter determined in parallel experiments conducted on the cloned muscarinic M(1)-M(5) subtypes in Chinese hamster ovary (CHO) cells. Furthermore, comparison of the gallbladder data with the dissociation characteristics of [3H]NMS in guinea pig urinary bladder revealed a significantly different kinetic profile, with the urinary bladder, but not the gallbladder, demonstrating biphasic radioligand dissociation kinetics. In functional experiments, carbachol caused a concentration-dependent contraction of guinea pig gallbladder smooth muscle strips in Ca(2+)-free or 5 mM Sr(2+)-substituted physiological salt solutions (PSS) with amplitudes of the maximal contractions corresponding to 45.8+/-8.0% and 33.2+/-6.6% of control responses in normal PSS, respectively. Furthermore, the stimulus-response characteristics of carbachol-mediated contraction appeared significantly altered in Ca(2+)-free PSS relative to normal or Sr(2+)-substituted PSS. The antagonist, methoctramine (1x10(-7)-3x10(-5) M), exerted only a slight inhibition of carbachol (10(-5) M)-induced contractions in 5 mM Sr(2+)-substituted medium, whereas it was significantly more potent in antagonizing gallbladder contractions in response to 10(-5) M carbachol in the absence of extracellular Ca(2+). Both atropine and tripitramine were equipotent in antagonizing carbachol-induced contractions in Ca(2+)-free (pIC(50): 6.85+/-0.11 for atropine and 5.75+/-0.32 for tripitramine) and Sr(2+)-substituted media (pIC(50): 6.88+/-0.25 for atropine and 5.70+/-0.16 for tripitramine), and pirenzepine was only slightly more potent in Ca(2+)-free PSS (pIC(50): 5.66+/-0.23) than in Sr(2+)-substituted PSS (pIC(50): 5.33+/-0.21). Taken together, our data indicate that carbachol contracts guinea pig gallbladder by stimulating two distinct muscarinic receptor subtypes linked to extracellular Ca(2+) influx and intracellular Ca(2+) release. These two subtypes may represent the muscarinic M(3) and M(4) receptors, although the presence of the muscarinic M(2) receptor subtype is also suggested from the binding data.
Keywords: Female; Humans; Animals; Male; Urinary Bladder; Muscle, Smooth; Receptors, Muscarinic; Gallbladder; Guinea Pigs; Muscle Contraction; Parasympatholytics; Muscarinic Antagonists; Cell Membrane; Muscarinic Agonists; Radioligand Assay; CHO Cells; Cricetinae; Calcium; N-Methylscopolamine